(untitled) (Revista Cientifica Ingenio Magno, 2020)
In the last 25 years, great progress has been made in the development of new materials, which have changed our lives or are in the process of changing them. The advance has been made mainly in work with materials on a nanometric scale, creating so-called nanomaterials because they are made up, in 50% or more, by particles that have at least one of their external dimensions at 100 nanometers [1]. Some of the applications of these materials are presented in the paragraphs below. In industrial applications, nanomaterials are used to make various products. In biology and medicine, magnetic nanoparticles have been used as drug carriers in the treatment of cancer, pathogen-detecting agents, also in the separation of proteins and as filter objects for molecules. Furthermore, nanowires have been manufactured from these materials, nanofibers and nanotubes, that allow observing and manipulating intracellular biological processes [2]. In the case of agriculture, preliminary studies have been carried out that show the potential of nanomaterials to improve germination and seed growth, plant protection, detection of pathogens and pesticide and herbicide residues [3]. One of the most promising and best developed environmental applications of nanotechnology has been environmental remediation and water treatment, where nanomaterials can help purify water through different mechanisms, including adsorption of heavy metals and other contaminants, contamination and inactivation of pathogens and the transformation of toxic materials into less toxic compounds [4]. Electrochemical energy storage technology is critically important to portable electronics, transportation, and large-scale energy storage systems. There is an increasing demand for energy storage devices with high energy density and high power, long-term stability, security and low cost [5]. As a solution to this demand, nanomaterials are very promising for the future, surface engineering advances in the development of materials with high energy storage capacity, fast recharge capacity and better durability [6] As a military application of nanomaterials, organic explosives are developed in the fine powder state, with submicron to nanoscale particle size distributions. Due to the complexity of manufacturing, a unique industrial method is created to produce these materials: the instant spray evaporation process, however, there is still the challenge of manufacturing objects with these explosive powders due to the balance that must be reached between power, safety and reliability. [7] Nanomaterials have become very useful tools in the fields of chemistry, materials science, physics, and nanotechnology due to their unique physical, chemical, magnetic, optical, and electronic characteristics. Along with the development of these materials, new manufacturing processes are created, as well as characterization techniques that specific their study and modifications.